Coordenaç\~ao do Bolsa Família nos sistemas de políticas públicas - Elaine Cristina Licio (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– Eradicating poverty is the first of the United Nations' Sustainable Development Objectives (ODS) for 2030. The Bolsa Família Program (BFP) is one of the main Brazilian initiatives in this regard, not only for the benefit paid to poor families, but also for promoting their prioritization for health, education and social assistance policies. The purpose of this paper is precisely to understand how these policies have been organized to serve the public PBF. In order to do so, we analyze the management of Bolsa Familia conditionalities within decentralized systems of education, health and social assistance, focusing on mobilized coordination mechanisms and consequent changes in the functioning of the policy to reach this public. It can be verified that the PBF has been able to enter the protocols, pacts and federative commitments of each articulated system, being, however, little debated in the respective structures of coordination. The program is also supported by financial incentives from the three policies, as well as mobilizing networks of managers at the three levels of government for their implementation in the areas of education and health. In addition, it has been producing changes in the way these policies work with the poorest public, through active search for specific offer and monitoring of the access of its beneficiaries. However, the results show that health policies, and especially social assistance policies, have yet to improve their mechanisms to broaden the coverage of the program's public supply and monitoring. In addition, the systematic use of the results of conditionalities management - understood as a diagnosis of the failures in the supply and monitoring processes - remains to be explored, in order to qualify the definition of intersectoral flows and protocols on how to act in the face of the situations encountered.
Keywords: I38; 330; Bolsa Família; federal coordination; articulation between services; benefits